Fluoxetine and citalopram exhibit potent antiinflammatory activity in human and murine models of rheumatoid arthritis and inhibit toll-like receptors. - Sacre, S; Medghalchi, M; Gregory, B; Brennan, F; Williams, R (2010)
OBJECTIVE: Selective serotonin reuptake inhibitors (SSRIs), in addition to their antidepressant effects, have been reported to have antiinflammatory effects. The aim of this study was to assess the antiarthritic potential of 2 SSRIs, fluoxetine and citalopram, in murine collagen-induced arthritis (CIA) and in a human ex vivo disease model of rheumatoid arthritis (RA). METHODS: Following therapeutic administration of SSRIs, paw swelling was assessed and clinical scores were determined daily in DBA/1 mice with CIA. Joint architecture was examined histologically at the end of the treatment period. Cultures of human RA synovial membranes were treated with SSRIs, and cytokine production was measured. Toll-like receptor (TLR) function was examined in murine and human macrophages, human B cells, and human fibroblast-like synovial cells treated with SSRIs. RESULTS: Both SSRIs significantly inhibited disease progression in mice with CIA, with fluoxetine showing the greatest degree of efficacy at the clinical and histologic levels. In addition, both drugs significantly inhibited the spontaneous production of tumor necrosis factor, interleukin-6, and interferon-gamma-inducible protein 10 in human RA synovial membrane cultures. Fluoxetine and citalopram treatment also inhibited the signaling of TLRs 3, 7, 8, and 9, providing a potential mechanism for their antiinflammatory action. CONCLUSION: Fluoxetine and citalopram treatment selectively inhibit endosomal TLR signaling, ameliorate disease in CIA, and suppress inflammatory cytokine production in human RA tissue. These data highlight the antiarthritic potential of the SSRI drug family and provide further evidence of the involvement of TLRs in the pathogenesis of RA. The SSRIs may provide a template for potential antiarthritic drug development.